(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2025)
This article describes an experimental technique that has had a positive effect on the physical fitness of skilled wrestlers. The technique involves breaking down complex moves into their component parts and drilling them with a partner until they can be executed without conscious thought. By doing this, wrestlers can become more efficient in their movements, making them more effective in matches without having to think about what they are doing. The article also emphasizes the importance of incorporating the technique into regular training to build muscle memory and increase reaction time. By mastering this technique, skilled wrestlers can improve their performance and achieve greater success in their matches.